Gestural and symbolic development among apes and humans: support for a multimodal theory of language evolution - Gillespie-Lynch, Kristen; Greenfield, Patricia M.; Lyn, Heidi; Savage-Rumbaugh, Sue (Frontiers in Psychology, 2014)
What are the implications of similarities and differences in the gestural and symbolic development of apes and humans? This focused review uses as a starting point our recent study that provided evidence that gesture supported the symbolic development of a chimpanzee, a bonobo and a human child reared in language-enriched environments at comparable stages of communicative development. These three species constitute a complete clade, species possessing a common immediate ancestor. Communicative behaviors observed among all species in a clade are likely to have been present in the common ancestor. Similarities in the form and function of many gestures produced by the chimpanzee, bonobo, and human child suggest that shared nonverbal skills may underlie shared symbolic capacities. Indeed, an ontogenetic sequence from gesture to symbol was present across the clade but more pronounced in child than ape. Multimodal expressions of communicative intent (e.g., vocalization plus persistence or eye-contact) were normative for the child, but less common for the apes. These findings suggest that increasing multimodal expression of communicative intent may have supported the emergence of language among the ancestors of humans. Therefore, this focused review includes new studies, since our 2013 article, that support a multimodal theory of language evolution.